Tinjauan Yuridis Terhadap Pelaku Flexing Media Sosial Terkait Arisan Bodong Di Kabupaten Karo - Silalahi, Taruli Silalahi (Albayan Journal of Islam and Muslim Societies, 2025)
This study aims to provide a juridical analysis of the flexing phenomenon on social media used as a method of fraud in illegal online rotating savings (arisan bodong) in Karo Regency. Flexing refers to the act of displaying wealth or a luxurious lifestyle in a manipulative manner to build a credible image and gain public trust, especially within online savings groups. The research employs a descriptive qualitative approach with data collection techniques including interviews, documentation, and literature review. Findings indicate that perpetrators of flexing may be prosecuted under Article 378 of the Indonesian Criminal Code (fraud), Article 28(1) of the Electronic Information and Transactions Law (ITE Law), and the Consumer Protection Law, although no specific regulation yet explicitly governs fraud based on flexing. Major challenges in law enforcement include difficulties in digital evidence collection, low legal literacy among victims, and limited capacity of law enforcement agencies in handling cybercrime. Thus, legal reform and strengthened digital consumer protection systems are urgently needed to prevent the recurrence of such fraudulent practices in the future.